Strategi Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Digital Pada Coffeeshop Terasore Medan - Vella Aticha; Abdul haris; Effiati Juliana Hasibuan (Universitas Medan Area, 2022)
The coffee trend is currently global and the rise of coffeeshops in various regions including the city of Medan, the interest of researchers in conducting this research is that the Medan Terasore Coffeeshop is one of the most popular coffeeshops among young people today. The Medan Terasore Coffeeshop is always crowded with young people, especially on weekends. The objectives of this research are as follows: To find out what strategies are carried out by Coffeeshop Terasore Medan in utilizing Instagram as a digital marketing communication medium. To find out what factors are the obstacles in carrying out the Instagram utilization strategy carried out by Coffeeshop Terasore Medan. This research uses descriptive qualitative research methods. Qualitative descriptive research method is a research method used to conduct research naturally. The results of the study show that the strategy of using Instagram social media through the from of posting photos, stories and video content has been successfully carried out by Coffeeshop Terasore Medan, with success being able to increase visitors who are increasing every day, especially at night. The inhibiting factor in carrying out the Instagram utilization strategy carried out by Coffeeshop Terasore Medan is that it does not have obstacles, it can be seen that with the uploads made by the admin of the Instagram account, Coffeeshop Terasore Medan is able to attract every visitor or follower to uploads that are in accordance with the topic being discussed. served on Instagram @terasore__.